Kebijakan Mitigasi Kebakaran Hutan Dan Lahan Berbasis Pemberdayaan Desa Wisata Digital Sadar Bencana (DWDSB) Di Riau - Syamsuadi, Amir; Arisandi, Diki; Hartati, Seri; Trisnawati, Liza; Elvitaria, Luluk; Nugroho, Sapto Setyo (Universitas Pahlawan Tuanku Tambusai, 2023)
Riau Province is confirmed as the largest and most affected area by forest fires from 2015. This study aims to look at forest fire disaster mitigation based on social engineering of tourism villages based on economic empowerment in Riau Province. The method used in this research is mix method, which is a combination of quantitative and qualitative approaches. This research explains the Disaster Mitigation Policy Model for Forest and Land Fires in Disaster Aware Digital Tourism Village (DWDSB) Based on Economic Empowerment in Riau by describing the mitigation policy for forest and land fires (karhutla), the level of village readiness in facing forest and land fires and the analysis of disaster-aware digital tourism villages (DWDSB) on local economic empowerment in Riau. The results showed that Riau Governor Regulation Number 9 of 2020 became the legal basis for the Riau Province Regional Disaster Management Agency (BPBD) in the aspect of forest and land fire disaster mitigation. The results also show that the Disaster Aware Digital Tourism Village (DWDSB) can be an alternative to developing disaster mitigation-based social engineering policies through green economy-based community empowerment activities based on local wisdom.